Clinical features and outcome of patients with cutaneous melioidosis during a nosocomial outbreak in a temperate region of Australia. Issue 4 (6th April 2018) - Clark, Benjamin; Merritt, Adam; Inglis, Tim; Manning, Laurens
Abstract: Six cases of cutaneous melioidosis from southwestern Australia, a non‐endemic region occurred as a result of Burkholderia pseudomallei contamination of normal saline that was used for irrigating superficial wounds. Treatment with parenteral meropenem, given by continuous infusion for 2 weeks, followed by oral antibiotics was successful in all cases.